2016
DOI: 10.1248/cpb.c16-00308
|View full text |Cite
|
Sign up to set email alerts
|

Design and Syntheses of Novel Fluoroporphyrin–Anthraquinone Complexes as Antitumor Agents

Abstract: A novel fluoroporphyrin-anthraquinone hybrid with dipeptide link and its metal complexes were synthesized and evaluated for anti-proliferation activity in human cancer cell line HeLa. The preliminary results demonstrated that all the compounds showed moderate to excellent antitumor activities. Among the active compounds, compound 3 which contains fluorinated porphyrin-anthraquinone and zinc ion exhibited the highest potency with IC 50 value of 8.83 µM, indicating that it was a promising antitumor candidate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Moreover, 9,10-anthraquinones can also be used to tag other molecules, e.g. a novel compound composed of porphyrin and a 9,10-anthraquinone derivative was synthesized to evaluate the anti-proliferation activity in HeLa cells ( Yang et al, 2016 ). Interestingly, the three 9,10-anthraquinones found in this study were observed to be osteophilic.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, 9,10-anthraquinones can also be used to tag other molecules, e.g. a novel compound composed of porphyrin and a 9,10-anthraquinone derivative was synthesized to evaluate the anti-proliferation activity in HeLa cells ( Yang et al, 2016 ). Interestingly, the three 9,10-anthraquinones found in this study were observed to be osteophilic.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Amino-substituted anthraquinones are used to composite porphyrin-anthraquinone hybrids, which are efficient photocleavage agents of DNA. [4][5][6][7] The key to efficient photocleavage is the charge transfer efficiency. [8][9][10][11][12][13] The -NH 2 and -NO 2 groups play a role in a strong electronic donor and acceptor in intramolecular charge transfer, respectively.…”
Section: Introductionmentioning
confidence: 99%